Maximizing the Use of Educational Media in Forming Anti-Bullying Values in School in Post-Truth Era - Nurdianzah, Erry; Azizah, Nurul; Zulfa, Laila Ngindana; Choiron, Miftakhul; Churironnafsi, Sajidah (Atthulab: Islamic Religion Teaching and Learning Journal, 2024)
Post truth is a phenomenon in which a person's mindset is formed by various information that is often displayed in various media. This phenomenon marks the importance of media in forming beliefs, so that ultimately moves someone to act. This theoretical research aims to determine how media can be used to instill anti-bullying values in schools. This research is qualitative research with a literature review approach, where the data sources come from books and journals that are appropriate to the topic of discussion. The data and information obtained were then collected, coded and appropriate themes were searched for and then analyzed. The research results show that; Forms of bullying at school have occurred in several forms, namely: verbal, physical, social, cyber, sexual. So this needs to be addressed immediately by instilling anti-bullying values, which can be done using educational media. Maximizing the use of educational media is an effective way in the post truth era to instill anti-bullying values in schools. This is because, in this era, the form of information in the media has become a determinant and is able to shape a person's mindset to act.Post truth merupakan fenomena dimana pola pikir seseorang terbentuk dari berbagai informasi yang sering ditampilkan di berbagai media. Fenomena ini menandai pentingnya media dalam membentuk keyakinan, yang mana hal tersebut mampu menggerakkan seseorang untuk bertindak. Penelitian teoritik ini bertujuan untuk mengetahui penggunaan media bisa digunakan dalam menanamkan nilai-nilai anti bullying di sekolah. Penelitian ini merupakan penelitian kualitatif dengan pendekatan literatur review, dimana sumber datanya berasal dari buku dan jurnal yang sesuai dengan topik pembahasan. Data dan informasi yang diperoleh kemudian dikumpulkan, diberi kode dan dicari tema yang sesuai lalu dianalisis. Hasil penelitian menunjukkan bahwa; Bentuk-bentuk bullying di sekolah terjadi dalam beberapa bentuk yaitu: verbal, fisik, sosial, cyber, seksual. Sehingga hal ini perlu segera diatasi dengan penanaman nilai-nilai anti bullying yang dapat dilakukan melalui media pendidikan. Pemaksimalan penggunaan media pendidikan menjadi salah satu cara yang efektif di era post truth dalam menanamkan nilai-nilai anti bullying di sekolah. Hal ini dikarenakan, bahwa pada era ini segara bentuk informasi di media sudah menjadi penentu dan mampu membentuk pola pikir seseorang untuk bertindak.